Models of technological development: The influence of investment structure - Vilhelmina V. Glazunova; Oleg S. Sukharev (Journal of New Economy)
The problem of refining Russia’s model of economic development through achieving the technological sovereignty dictates the need for making strategic decisions within the investment policy of economic growth. The paper aims to determine the models of technological modernisation according to the structure of investments in “old – new” technologies and develop an algorithm for identifying these models by assessing the relationship between investment and risk. Methodologically, the study rests on the theory of technological change. The paper employs elements of structural, statistical, regression and econometric analysis, as well as applies taxonomy methods to pinpoint various options for investment and technological modernisation models. T he evidence is the data on the investment in fixed assets and expenditures on tech nological innovations for 2010–2022 coming from the Federal State Statistics Service of the Russian Federation. The result is the identification of a model of technological modernisation in the Russian economy according to the structure of investments in “old – new” technologies and the sensitivity of the general technological intensity to investments. The paper distinguishes four general strategies of technological devel opment by the impact of expenditures on the dynamics of technological intensity, namely “leadership”, “breakthrough”, “giving up”, and “degradation”. Then, accord ing to the impact of investment in new technologies on technological modernisation it justifies the models “blockage”, “rigidity”, “modernisation”, “saturation”, and, in a similar manner, validates the models “degradation”, “backwardness”, “reliance on old technologies”, “reliance on new technologies” according to the impact of investment in old technologies on technological modernisation. The paper constructs a theoreti cal model of the connection between investment and risk, institutional parameters of investment process. The findings reveal that the Russian economy follows the model of backwardness with local technological innovations, which requires a massive in crease in investment in new technologies, mitigation of risks, and modification of institutional conditions.